Petrogenesis of the peralkaline Dutsen Wai and Ropp complexes in the Nigerian younger granites: implications for crucial metal enrichments. Issue 16 (2nd November 2021) - Amuda, Abdulgafar Kayode; Yang, Xiaoyong; Deng, Jianghong; Faisal, Mohamed; Cao, Jinya; Bute, Saleh Ibrahim; Girei, Musa Bala; Elatikpo, Safiyanu Muhammad
ABSTRACT: The Dutsen Wai and Ropp complexes are parts of the over 50 within-plate alkaline ring complexes in north-central Nigeria. These complexes consist mainly of A-type granites that were emplaced between 175 Ma (in Dutsen Wai) and 149 Ma (in Ropp). They are characterized by moderately negative zircon ԑHf (t) values (–9.8 to – 5.86) with Paleoproterozoic (1597–1884 Ma) crustal model ages (TDM c), suggesting the mantle-derived parental magmas have been substantially modified by assimilation of crustal materials. The granites exhibit elevated HFSEs (e.g., Nb and Zr) and LILE (e.g., Rb and REE) concentrations, with higher values in the peralkaline than in the aluminous granites, but are depleted in compatible elements (e.g., CaO, MgO, Ba and Sr). This is typical of highly differentiated granites associated with rare metal mineralization. The peralkaline plutons show REE patterns with strong negative Eu anomalies, significant M-type lanthanide tetrad effect (TE1, 3  = 1.16–1.32), and non- CH arge and R adius C ontrolled (CHARAC) behaviour of some HFSEs. The positive correlation of Na2 O vs. Nb ( r 2  = 0.92) and Nb vs. TE1, 3 ( r 2   = 0.7), increasing degree of albitization and shift in eutectics of granite minimum towards Ab-Qtz sideline indicate that Na-rich fluid plays an important role in the complexation between F and other incompatible elements in open system processes. Fluorine also favoured the retention of these crucial metals in the peralkaline melt until late magmatic-stage during which the breakdown of the F-HFSEs and F-REE complexes was accompanied by crystallization of pyrochlore and REE-bearing accessory minerals. We proposed that the emplacement of these A-type granites was probably linked to the prevailing transtension regime before the fragmentation of Gondwana during the Mesozoic period which reactivated some deep-seated Pan-African transcurrent faults. This, in turn, caused pressure release and channelled fluid, which triggered partial melting of the lower part of the lithospheric mantle.